1987
DOI: 10.1177/030089168707300402
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Serum Alkaline Phosphatase in Osteosarcoma

Abstract: In 163 patients with osteosarcoma of the extremities treated with adjuvant chemotherapy, serum alkaline phosphatase (SAP) levels were evaluated before treatment and successively closely monitored in an attempt to determine whether serum levels of this enzyme had clinical value in predicting the course of the disease. Of 121 patients with elevated preoperative SAP levels, 78 (64%) recurred. Of 42 patients with normal preoperative SAP levels, only 8 (19%) recurred (P less than 0.00001). Of the 140 patients local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Previous studies of many investigators showed that the plasma total ALP activity raised to an abnormal level at the time of recurrence or metastasis [1,16,19], In the present study, we also found that the plasma BALP levels of the patients at the time of recurrence were significantly higher than those of the patients without evidence of recurrence at the time of follow-up consultations ( fig. 1).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies of many investigators showed that the plasma total ALP activity raised to an abnormal level at the time of recurrence or metastasis [1,16,19], In the present study, we also found that the plasma BALP levels of the patients at the time of recurrence were significantly higher than those of the patients without evidence of recurrence at the time of follow-up consultations ( fig. 1).…”
Section: Discussionsupporting
confidence: 82%
“…In patients with osteosarcoma, a disease of abnormally high production of osteoid or im mature bone, there is fairly good correlation between the activity of plasma total ALP and the degree of osteoblastic activity in the tumor. Many investigators reported that 40-80% of the patients with osteosarcoma have abnor mally elevated activity of plasma total ALP [1,[14][15][16][17], However, data concerning the status of bone-specific 278 Oncology 1996;53:275-280 Liu/Leung/Kum ta/Lee/Fung isoenzyme in the plasma of thee patients are lacking. As the tissue-specific isoenzyme of ALP may reflect the activity of the osteosarcoma cells more accurately, BALP activity should be measured instead of the total plasma ALP activity which may be affected by factors other than those from the bone.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs with an increased AP value did not benefit from additional chemotherapy, but dogs with an AP value within the normal range did benefit, similar to the situation for human OS. 1,2 The source of the elevated AP value in dogs is bone-specific AP, which is produced by the neoplastic osteoblasts. 12 In the present study, the specific isoenzymes were not determined.…”
Section: Discussionmentioning
confidence: 99%
“…14 Several studies have revealed that in human patients receiving surgery and chemotherapy, recurrence rates are higher among patients with increased TALP activity before treatment than among patients with normal activity. [15][16][17] At the time of diagnosis, human patients with clinically detectable metastases are more likely than patients with localized disease to have increased TALP activity. 17 Activity of TALP in the early period after treatment has not been revealed to correlate with survival, 15,17 although development of increased TALP activity during follow-up often heralds the appearance of clinically apparent metastases or local tumor recurrence.…”
mentioning
confidence: 99%